Digital literacies social learning and classroom practices - Carrington, Victoria; Robinson, Muriel; Sage eBooks; United Kingdom Literacy Association (London : SAGE, 2009)
Digital technologies are an everyday part of life for students and this text explores the ways in which they can be used in schools. The authors provide an insight into the research on digital technologies, stressing its relevance for schools, and suggest ways to develop new, more relevant pedagogies.
Published in association with the United Kingdom Literacy Association.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Computer-assisted instruction; Teaching -- Computer network resources; Online social networks; Educational innovations; Electronic books